2020
DOI: 10.1177/0886260520935093
|View full text |Cite
|
Sign up to set email alerts
|

Context, Types, and Consequences of Violence Across the Life Course: A Qualitative Study of the Lived Experiences of Transgender Women Living With HIV

Abstract: Violence is a known driver of HIV vulnerability among transgender (trans) women, who are disproportionately impacted by HIV globally. Violence is also a barrier to accessing HIV prevention, treatment, and support. Yet, little is known about the everyday experiences of violence faced by trans women living with HIV, who live at the intersection of a marginalized gender identity and physical health condition. To address this gap, this study draws on semi-structured, individual interviews conducted 2017–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…[39][40][41][42][43] Transwomen also had higher rates of mental health diagnoses, which are well-documented and attributed to the effects of minority stress, socioeconomic disparities, violence, family rejection, and gender dysphoria. 14,42,[44][45][46][47][48][49][50][51][52][53] Mental health diagnoses have also been identified as a barrier to successful treatment of HIV. 42,54 Furthermore, transwomen had significantly more SUD diagnoses than cis-SMM.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43] Transwomen also had higher rates of mental health diagnoses, which are well-documented and attributed to the effects of minority stress, socioeconomic disparities, violence, family rejection, and gender dysphoria. 14,42,[44][45][46][47][48][49][50][51][52][53] Mental health diagnoses have also been identified as a barrier to successful treatment of HIV. 42,54 Furthermore, transwomen had significantly more SUD diagnoses than cis-SMM.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2020, several studies have documented associations between personal encounters with the police and negative mental health outcomes in multiple populations (Table 3) [29,33,38,61–64,65 ▪▪ ,66–70,71 ▪ ,72,73 ▪▪ ]. Remch et al [65 ▪▪ ] found that in a longitudinal cohort of Black MSM ( n = 1155), those who experienced police harassment in the past 6 months had a 1.63 (95% CI 1.32–2.02) times higher rate of psychological distress, but not a higher rate of depressive symptoms.…”
Section: Police Encountersmentioning
confidence: 99%
“…Research with transgender women living with HIV found that when trans participants had to leave home because of family violence, which was often driven by transphobia, they were then unable to find employment because of transphobic discrimination, which ultimately led to homelessness and engagement in sex work (Lacombe-Duncan & Olawale, 2022). Homelessness and engagement in sex work then increased these women's vulnerability to police violence and HIV (Lacombe-Duncan & Olawale, 2022). In one study comparing healthcare outcomes and access for transgender and cisgender adolescents who had run away from home, transgender adolescents reported worse overall health, were more likely to have forgone needed medical care, and received less helpful care from medical providers than their cisgender peers (M. Ferguson et al, 2022).…”
Section: Abstract Transgender Lgbt Homelessness Family Suicide Chosen...mentioning
confidence: 99%